Characterization of colonization kinetics and virulence potential of Salmonella Enteritidis in chickens by photonic detection - Wellawa, Dinesh H.; Lam, Po-King S.; White, Aaron P.; Allan, Brenda; Köster, Wolfgang (Frontiers in Veterinary Science, 2022)
The light emitting module lux operon (luxCDABE) of Photorhabdus luminescens can be integrated into a “dark” bacterium for expression under a suitable promoter. The technique has been used to monitor kinetics of infection, e.g., by studying gene expression in Salmonella using mouse models in vivo and ex vivo. Here, we applied the bioluminescence imaging (BLI) technique to track Salmonella Enteritidis (SEn) strains carrying the lux operon expressed under a constitutive promoter sequence (sigma 70) in chicken after oral challenge. Detectable photon signals were localized in the crop, small intestine, cecum, and yolk sac in orally gavaged birds. The level of colonization was determined by quantification of signal intensity and SEn prevalence in the cecum and yolk sac. Furthermore, an isogenic SEn mutant strain tagged with the lux operon allowed for us to assess virulence determinants regarding their role in colonization of the cecum and yolk sac. Interestingly, mutations of SPI-1(Salmonella Pathogenicity Island 1) and fur (ferric uptake regulator) showed significantly decreased colonization in yolk sac that was correlated with the BLI data. A similar trend was detected in a ΔtonB strain by analyzing enrichment culture data. The inherently low quantum yield, light scattering, and absorption by tissues did not facilitate detection of signals from live birds. However, the detection limit of lux operon has the potential to be improved by resonance energy transfer to a secondary molecule. As a proof-of-concept, we were able to show that sensitization of a fluorescent-bound molecule known as the lumazine protein (LumP) improved the limit of detection to a certain extent.